2015
DOI: 10.1021/acs.orglett.5b02983
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(0)/N-Heterocyclic Carbene-Catalyzed Asymmetric [2 + 2 + 2] Cycloaddition of Two Enones and an Alkyne: Access to Cyclohexenes with Four Contiguous Stereogenic Centers

Abstract: A nickel(0)/chiral N-heterocyclic carbene (NHC)-catalyzed fully intermolecular, enantioselective [2 + 2 + 2] cycloaddition of two enones and an alkyne has been developed to access enantioenriched cyclohexenes. A single diastereomer was obtained with a successive generation of four contiguous stereogenic centers. The absolute configuration of cyclohexene derivative 3aa was determined by X-ray diffraction and circular dichroism (CD) spectral studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 54 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…14 First, we examined the reaction with N-biphenyl-2-yl-substituted NHC L*1, which was an optimal ligand in the case of our Ni(0)-catalyzed enantioselective [2+2+2]-cycloaddition reaction. 13 However, this NHC did not give 3aa at all. In a similar manner, N-2-isopropylphenyl-12d and N-1-naphthylsubstituted NHCs L*2 and L*3 were also unsuccessful, which suggested that mono-ortho-substituted NHCs might not be suitable to deliver the desired product, 3aa.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…14 First, we examined the reaction with N-biphenyl-2-yl-substituted NHC L*1, which was an optimal ligand in the case of our Ni(0)-catalyzed enantioselective [2+2+2]-cycloaddition reaction. 13 However, this NHC did not give 3aa at all. In a similar manner, N-2-isopropylphenyl-12d and N-1-naphthylsubstituted NHCs L*2 and L*3 were also unsuccessful, which suggested that mono-ortho-substituted NHCs might not be suitable to deliver the desired product, 3aa.…”
mentioning
confidence: 81%
“…12 Very recently, we explored the Ni(0)-catalyzed enantioselective [2+2+2] cycloaddition of two enones and an alkyne in the presence of a chiral NHC [Scheme 1,(3)]. 13 Herein, we report the development of an enantioselective variant of a Ni(0)-catalyzed [2+2] cycloaddition of α,β-unsaturated carbonyls with 1,3-enynes to produce enantioenriched cyclobutenes [Scheme 1,(1)].…”
mentioning
confidence: 99%
“…The multi-substituted cyclohexenes bearing four contiguous chiral centers 137 were obtained in moderate to good yields and ee values (Scheme 44). 87 2.10.3 Construction of four-membered carbocyclic skeletons. In 2019, Sensuke Ogoshi et al reported that they successfully constructed the four-membered carbocyclic skeleton employing NHC C41-Ni cooperative catalysis through [2 + 2] annulation between 1,3-enynes and a,b-unsaturated carbonyls 138, leading to a series of enantioenriched cyclobutenes 139 (Scheme 45).…”
Section: Applications In the Construction Of Several Complex Carbocyclic Skeletonsmentioning
confidence: 99%
“…13 ). 87 Therefore, the construction of carbocyclic skeletons has achieved considerable attention. 88 For NHCs, there have been increasing applications in the synthesis of almost all types of cyclic compounds, and they are also widely used in the synthesis of carbocyclic skeletons.…”
Section: Applications Of Nhcs In the Construction Of Biologically Act...mentioning
confidence: 99%
See 1 more Smart Citation